Editorial: Gateway to monocyte entry into the brain: CXCR7, the new orchestra conductor. Issue 5 (1st November 2017) - Douglas, Steven D.; Spitsin, Sergei
Abstract : Discussion on the potential role for CXCR7 as a major signaling pathway for CD14 + CD16 + monocyte transmigration across the blood brain barrier, and its therapeutic application for NeuroAIDS.